Typhoid: Diagnosis and Treatment - Mzher, Zahraa Sadiq; Kadhim, Alzahraa Hazim; Yaman, Afif Taher; Mallh, Tabark Sajid; Mary, Zainab Qasim; Adhab, Samah Ahmed (American Journal of Biology and Natural Sciences, 2024)
Typhoid fever is most prevalent in the Asian part of the world especially in the developing countries of Asia like Pakistan and India, caused by a Gram-negative bacterium Salmonella enterica servar typhi. It is an orally transmitted communicable disease caused by consuming contaminated food and impure water. The incubation period of the disease is 7 to 14 days. Symptoms include high fever, rash, weakness, abdominal pain constipation, headache, and poor appetite. Antibiotic resistance is a major problem to treat it effectively. First line drugs are mostly not used to treat typhoid and the resistance is emerging in fluoroquinolones. The only choice of drug remaining is ceftriaxone and azithromycin. A counteractive action of typhoid fever is chiefly by individual and household cleanliness. The provision of clean water and safe disposal of faeces should be implemented to eradicate S. typhi. Good surveillance, better diagnostics, more sensible use of antibiotics and efficient vaccine will be significant to reduce the burden of disease caused by S. typhi.